Down-regulation of ATP-binding cassette transporter G1 expression by unmethylated CpG oligodeoxynucleotides in RAW 264.7 macrophages - Seo, Jeong Min (Korean Society for Biochemistry and Molecular Biology, 2011)
We have investigated the effect of various forms of phosphodiester cytidine-phosphate-guanosine oligodeoxynucleotides (CpG ODNs) on the production of pro-inflammatory cytokines and related genes in RAW 264.7 macrophages. Treatment with the CpG ODNs increased the expression of tumor necrosis factor α (TNF-α), IL-6, and inducible nitric oxide synthase but not interleukin-1β (IL-1β). We also investigated the effect of CpG ODNs on the expression of ATP-binding cassette transporter A1 (ABCA1) and G1 (ABCG1) genes which are known to facilitate cholesterol efflux from macrophages for anti-atherosclerosis. CpG 2006 significantly reduced the levels of ABCG1 mRNA as determined by real-time polymerase chain reaction, whereas ABCA1 mRNA level was not changed. Western blot analysis further confirmed the reduction of ABCG1 protein expression by CpG 2006. In addition, we also determined the protein level of peroxisome proliferator activated receptor γ (PPARγ), which is recognized as a transcriptional activator of ABC transporters, was also reduced by CpG 2006. Thus, these results suggest that ABCG1 is specifically down-regulated by CpG 2006 in a PPARγ-dependent manner in macrophages.